Nonergodicity in load and recovery: group results do not generalize to individuals - Neumann, N. D.; Van Yperen, N. W.; Brauers, J. J.; Frencken, W.; Brink, W. S.; Lemmink, K. A. P. M.; Meerhoff, L. A.; Den Hartigh, R. J. R. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The study of load and recovery gained significant interest in the last decades, given its important value in decreasing the likelihood of injuries and improving performance. So far, findings are typically reported on the group level, whereas practitioners are most often interested in applications at the individual level. Hence, the aim of the present research is to examine to what extent group-level statistics can be generalized to individual athletes, which is referred to as the "ergodicity issue." Nonergodicity may have serious consequences for the way we should analyze, and work with, load and recovery measures in the sports field.